A new catfish species of Microcambeva Costa & Bockmann 1994 (Siluriformes: Trichomycteridae) from a coastal basin in Rio de Janeiro State, southeastern Brazil - de Medeiros, Lucas Silva; Moreira, Cristiano Rangel; de Pinna, Mário; Lima, Sergio Maia Queiroz (Zootaxa, 2020)
Microcambeva bendego, a small psammophilous catfish species, is described from the rio Guapi-Macacu basin at Guanabara Bay in Rio de Janeiro State, an Atlantic Forest remnant. This coastal drainage has been explored by several naturalists and fish researchers since the 19th century. It is a drainage with remarkably high endemism and species richness, and some recently-described and threatened species. The new species is distinguished from all congeners by two distinctive characters: long finger-like projections in the branchial isthmus and a large opercular patch of odontodes with 19 odontodes. Due to the paucity of specimens (n=3) osteological features of the new species were accessed by CT-Scan images of the holotype. Microcambeva bendego shares putative synapomorphies with two congeners, M. ribeirae and M. filamentosa, such as the fusion of supraorbital pore s6, the absence of ossification in the anterior autopalatine cartilage, the presence of an elongated and wide posterior process of the autopalatine, and a concavity on the dorsal process of the opercle. Those characters suggest that M. bendego is more closely related to those two species from the rio Ribeira de Iguape basin than to other congeners. The biogeography and conservation status of M. bendego are also discussed.